PENGARUH KADAR INTERLEUKIN-6 DAN NEURON SPECIFIC ENOLASE TERHADAP LUARAN STROKE ISKEMIK AKUT - Al Rasyid; Salim Harris; Muhammad Kurniawan; Taufik Mesiano; Rakhmad Hidayat (NEURONA, 2018)
THE EFFECT OF INTERLEUKIN-6 AND NEURON SPECIFIC ENOLASE LEVEL ON ACUTE ISCHEMIC STROKE OUTCOME WITH PACS AND LACS SUBTYPEABSTRACTIntroduction: Brain blood flow disruption  in ischemic stroke will trigger  cells damage  cascade  and  caused infarction. Interleukin-6 (IL-6) and neuron specific enolase (NSE) are brain cells damage marker that can be markers of acute ischemic stroke outcome.Aim: To investigate the effect of IL-6 and NSE levels on acute ischemic stroke outcome and its interacting factors.Methods: An observational cohort study on ischemic stroke patients with onset ≤3 days in several hospitals in Jakarta and Depok in 2014. Medical history and physical examination were carried out as well as laboratory parameters; hematocrit, fibrinogen, low density lipoprotein (LDL), high density lipoprotein (HDL), triglyceride, IL-6, and NSE. The National Institute of Health Stroke Scale (NIHSS) were assessed ≤72 hours of onset and 7 days along with Modified Rankin Scale (mRS) at 1 month of onset. Bivariate and multivariate logistic regression were done to investigate the association of IL-6 and NSE with stroke outcome and other factors.Results: One-hundred thirty-five subjects were included, mostly male (62%), with age mean 59,4±10,7 years and subtype PACS (76%). Interleukin-6 and NSE level were elevated in 61,5% and 21,5% subjects. Interleukin-6 and fibrinogen influenced the mRS, while diabetes and fibrinogen influenced the NIHSS. NSE serum didn’t show any association with mRS nor NIHSS, but influenced by dyslipidemia.Discussion: There was a tendency of worse outcome on high IL-6 level patients, although by multivariate analysis IL-2 alone was not sufficient enough as prognostic marker in acute ischemic stroke outcome. Neuron specific enolase serum didn’t show any association with acute stroke outcome due to also influenced by sex, smoking, and fibrinogen levels.Keywords: Acute ischemic stroke, IL-6, NSE, outcomeABSTRAKPendahuluan: Gangguan aliran darah otak pada stroke iskemik akut akan memicu kaskade kerusakan sel otak yang menyebabkan infark dan inflamasi. Interleukin-6 (IL-6) dan neuron specific enolase (NSE) merupakan penanda kerusakan sel otak yang dapat menjadi penanda luaran stroke iskemik akut.Tujuan: Mengetahui pengaruh kadar IL-6 dan NSE pada luaran stroke iskemik akut serta faktor-faktor yang memengaruhinya.Metode: Penelitian kohort observasional terhadap pasien stroke iskemik akut dengan awitan ≤3 hari yang dirawat di beberapa RS di Jakarta dan Depok pada tahun 2014. Dilakukan anamnesis dan pemeriksaan fisik serta pemeriksaan hematokrit, fibrinogen, low density lipoprotein (LDL), high density lipoprotein  (HDL), trigliserida, IL-6, dan NSE serum. Dilakukan pemeriksaan National Institute of Health Stroke Scale (NIHSS) awal awitan ≤72 jam dan 7 hari serta modified rankin scale (mRS) pada 1 bulan. Analisis statistik bivariat dan regresi logistik multivariat dilakukan untuk mengetahui hubungan kadar IL-6 dan NSE dengan luaran stroke serta hubungannya terhadap faktor-faktor lainnya.Hasil: Didapatkan 135 subjek yang mayoritas laki-laki (62%) dengan rerata usia 59,4±10,7 tahun dan subtipe PACS (76%). Peningkatan kadar IL-6 dan NSE ditemukan pada 61,5% dan 21,5% subjek. Luaran berdasarkan skor mRS dipengaruhi oleh kadar IL-6 dan fibrinogen, sedangkan  berdasarkan NIHSS dipengaruhi oleh diabetes melitus dan fibrinogen. Kadar NSE tidak berhubungan dengan mRS dan NIHSS, namun dipengaruhi oleh status dislipidemia.Diskusi: Terdapat kecenderungan luaran buruk pada kadar IL-6 tinggi, namun dengan analisis multivariat IL-6 belum bisa menjadi penanda prognosis luaran stroke iskemik akut. Kadar NSE serum tidak berperan terhadap luaran stroke iskemik akut, oleh karena juga dipengaruhi oleh jenis kelamin, merokok, dan kadar fibrinogen.Kata kunci: Stroke iskemik akut, IL-6, neuron specirefic enolase, luaran